Air exchange rates from atmospheric CO(2) daily cycle - Carrilho, João Dias (Energy Build, 2015)
We propose a new approach for measuring ventilation air exchange rates (AERs). The method belongs to the class of tracer gas techniques, but is formulated in the light of systems theory and signal processing. Unlike conventional CO(2) based methods that assume the outdoor ambient CO(2) concentration is constant, the proposed method recognizes that photosynthesis and respiration cycle of plants and processes associated with fuel combustion produce daily, quasi-periodic, variations in the ambient CO(2) concentrations. These daily variations, which are within the detection range of existing monitoring equipment, are utilized for estimating ventilation rates without the need of a source of CO(2) in the building. Using a naturally-ventilated residential apartment, AERs obtained using the new method compared favorably (within 10%) to those obtained using the conventional CO(2) decay fitting technique. The new method has the advantages that no tracer gas injection is needed, and high time resolution results are obtained.